Endoscopic resection for gastrointestinal neuroendocrine tumors - Boškoski, Ivo; Volkanovska, Anche; Tringali, Andrea; Bove, Vincenzo; Familiari, Pietro; Perri, Vincenzo; Costamagna, Guido (Informa UK Limited, 2014)
Gastrointestinal (GI) and neuroendocrine tumors (NETs) can be treated by mini-invasive endoscopic resection when localized in the superficial layers of the bowel wall and their size is <20 mm. Endoscopic diagnosis of NETs is usually incidental or suspected after clinical, laboratory or imaging findings. Endoscopic mucosal resection is the most commonly used technique for NET removal, endoscopic submucosal dissection is indicated in selected cases, while papillectomy is feasible for ampullary lesions. Histopathologic assessment of the resection margin (circumferential and deep) is important for staging. Incidence of endoscopic mucosal resection-/endoscopic submucosal dissection-related complications for removal of GI NETs are similar to those reported for other GI lesions. Endoscopic follow-up is based on histopathologic characteristics of the resected NETs and its site. NETs >20 mm in size, with penetration of the muscle layer and/or serosa are at high risk for metastases and surgical approach is recommended when feasible.
Keywords: ampullectomy; endoscopical mucosal dissection; endoscopic mucosal resection; gastrointestinal; neuroendocrine tumors